Cultural political economy, crisis management, and COVID-19 in the United States. Issue 1 (2nd January 2022) - Mueller, Jason C.
ABSTRACT: The Coronavirus Disease 2019 (COVID-19) has ravaged the world. The pace at which this pandemic spread left policy makers scrambling to understand the virus and craft ameliorative policy measures, while populations struggled to make sense of the pandemic's impact on their lives. This opened up many opportunities for crisis learning. This article deploys the Cultural Political Economy (CPE) approach to analyse discursive and material ways in which the President of the United States engaged in crisis learning and crisis management during the early months of the pandemic. Although preexisting conditions structured the early response to COVID-19, contingent moments of (in)action by the President had significant, path-shaping impact on the scope and severity of the pandemic. A vignette on the functionality of the US healthcare system during the early days of the pandemic offers further clarity on the interplay between material and discursive factors impacting real-time crisis learning and management.